(untitled) - Ashley, A. (New York, 2003)
Contents: Letters, faxes.and emails; Content and style; Enquiries; Repliesand quotations; Orders; Payment; Complaints and adjustments; Credit; Banking; Agentsandagencies so; ransportationandshipping Insurance; Miscellaneouscorrespondence; Memosandreports; Personnelappointments
Keywords: Business letters,Commercial correspondence,Thư tính thương mại,Thư tính thương mại